Coding activities for building apps with Python - Small, Cathleen (Code creator (Rosen Publishing Group), 2022)
"Readers will learn how to code using Python, a popular and highly functional programming language. Readers will code short programs that perform mathematical computations, compare data, store variables, and even produce simple games"--Amazon.